HUBUNGAN PERSEPSI KEIKUTSERTAAN DALAM KEGIATAN EKSTRAKURIKULER PRAMUKA DAN PEMAHAMAN NILAI SEJARAH DENGAN SIKAP NASIONALISME SISWA KELAS X IPS SMA NEGERI 6 SURAKARTA TAHUN AJARAN 2015/2016 - Bagas, Arga; Suryani, Nunuk; Mussadad, Akhmad Arif (Candi, 2018)
The purpose of this research are: 1) To determine the relationship perception of participation in scout extracurricular activities with students? nationalism class X IPS SMA Negeri 6 Surakarta. 2) To determine the relationship of historical value?s comprehension with students? nationalism class X IPS SMAN 6 Surakarta. 3) To determine the relationship perception of participation in scout extracurricular activities and historical value?s comprehension with students? nationalism class X IPS SMA Negeri 6 Surakarta.This research is descriptive quantitative research by drawing conclusions through statistical analysis. The population in this study were all students of class X IPS SMA Negeri 6 Surakarta. Samples taken as many as 83 by using simple random sampling technique. Necessary data obtained through a questionnaire. The questionnaire previously tested and tested for validity and reliability test. Data analysis technique used is multiple linear regression analysis, t-test, F, R2 test and the relative contribution and effective contribution.The conclusion of this study were: 1) There is a significant and positive relationship in perception of participation in scout extracurricular activities with students? nationalism class X IPS SMA Negeri 6 Surakarta. This is based on multiple linear regression analysis (t test) note that tcount> ttable, 7.253> 1.664 and significance value 0.000<0.005 with the relative contribution of 77.71% and effective contribution 41.11%. 2) There is a significant and positive in historical value?s comprehension with students? nationalism class X IPS SMA Negeri 6 Surakarta. This is based on multiple linear regression analysis (t test) note that tcount> ttable, 3.055> 1.664 and significance value 0.003<0.005 with the relative contribution of 15.18% and the effective contribution of 8.03%. 3) There is a positive and significant in perception of participation in scout extracurricular activities and historical value?s comprehension along with students? nationalism class X IPS SMA Negeri 6 Surakarta. This is based on linear regression analysis (F test) known that F count> F table, is 44.973>3.960 and significance value 0.000<0.05. The coefficient of determination (R2) of 0.529 indicates that the magnitude of the relationship perception of participation in scout extracurricular activities and historical value?s comprehension with students? nationalism class X IPS SMA Negeri 6 Surakarta academic year 2015/2016 was 52.9%, while the rest influenced by other variables.